O papel da iniciativa pública na produção nacional de games - Linzmayer, Gustavo de Castro (2014)
To fulfill its purpose, we will get this work started from the present conditions of the national videogame production. That is a rising industry with increasing attention from the national state because of its potential in many aspects, such as the economical, educational and artistic ones. At the same time, the industrial polices are restricted and discontinuous and the development experiences take place with a great deal of inequality, and the production is concentrated mostly in some specific locations, without a large development tradition. Because of that, we have chosen to carry out case studies about videogames produced with support resources from state agencies industrial polices. Thus, we search to analyze the effects of these initiatives in specific videogames, on their inherent content and form as well as aspects such as their team design, work method, their relationship with supporters and the task of videogame advertising and distribution. We search, in this sense, to understand how state oriented industrial policy can be seized, what are the difficulties faced by producers, the result oriented most successful ways of conduct and the mistakes that were made along the way. Such a manner, we propose to indicate some possible coordinates and prospects for the foreseeable future of the national videogame production.